ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI PADI SAWAH DI DESA POLEGANYARA KECAMATAN PAMONA TIMUR KABUPATEN POSO - Neni Hasrani T; Dance Tangkesalu (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
This study aims were to identify the use of production inputs and to determine the price efficiency of the wetland rice farming system in Poleganyara Village. This study was conducted from August to December 2013. The number of respondents was 31 people selected through simple random sampling.  Data collected was analyzed using Cobb-Douglas production function, income analysis and efficiency analysis. The research results showed that the inputs used had covered the cost spent.  The average income of the respondents was IDR 14,489,761.09 planting season-1 (PT) greater    than the total expenditure of IDR 6,683,795.22 PT-1 thus resulting in the benefit of IDR 7,805,965.87 PT-1 under land area size of 0.95 ha. All inputs used as independent variables (X) were both partially and simultaneously affected the dependent variable (Y) significantly at α level of 1%.  The efficiency analysis indicated that such variables as land area, seeds, and fertilizer were not yet efficient (tcal>ttab) while labor was already efficient. Key Words : Efficiency, income, and wetland rice.